Perlindungan Hukum Bagi Debitur Dari Kerugian Akibat Perjanjian Kredit Yang Tidak Sesuai Dengan Offering Letter - Dwi Lestarini, Geri (Universitas Negeri Malang, 2020)
This study aimed to analyze legal protection for debtors who experienced losses due to the credit agreement which was different from the offering letter. The credit agreement was a principal agreement that governed the rights and responsibilities between creditors and debtors. This study was a normative juridical study, which was then analyzed using descriptive qualitative methods. The search results showed that the bank includes a standard clause in the credit agreement deed, which was different from the offering letter. The existence of these standard clauses violated applicable regulations and prejudiced the debtor. There was legal protection both preventive and repressive provided by laws and regulations for protecting debtors from losses due to standard clauses that were not in the offering letter.